Incorporating strategic management and competitive intelligence into library practice - Olabisi Fadeke Adesina; Zainab Olanihun Ambali; Medinat Dolapo Laaro; Tunde Toyese Oyedokun (Northern Negros State College of Science and Technology (NONESCOST), 2022)
In the information value chain, libraries face competition from the Internet and web information providers, including online information vendors, information brokers, and others. To stay ahead of their rivals, libraries must use strategy and intelligence gathering to ensure dynamic information services that can meet a wide range of current and emerging users' information needs. This is especially important in an environment where libraries' operations are growing more challenging and competitive. This study is a review article that provides an overview of current thinking on the applicability of strategic management and competitive intelligence to contemporary library practice, as well as a critical examination of prior studies, opinions, and research. According to reports, competitive intelligence is a tactical endeavour that is closely related to and integrated with librarianship. Competitive intelligence in libraries comprises determining user profiles and information needs, as well as gathering and analysing external data to plan for the competitive delivery of information services. For a very long time, people have viewed librarians as gatekeepers who serve as intermediaries between information users and the world of information. Changes in information sources, management techniques, and advancements in information technology are converting the library's intermediary function into an enabler, providing the instruments to distribute information more rapidly and directly. To maintain or improve libraries' level of competitiveness on a global scale, it is crucial to emphasize the importance of competitive intelligence in modern information delivery as a synergy to expand intelligence availability.